PENDIDIKAN KARAKTER MELALUI INTEGRASI PROFIL PELAJAR PANCASILA DALAM KURIKULUM MERDEKA DI KABUPATEN PANGANDARAN - Dewi, Dinie Anggraeni; Yuniarti, Yeni; Adriansyah, Muhammad Irfan; Herlambang, Yusuf Tri; Rostika, Deti; Istiqomah, Yunita Yasmin; Sukawan, Intan Afiyah (Abdi Panca Marga, 2023)
The rise of juvenile delinquency, such as the culture of cheating, drugs, motorbike gangs, free sex, and bullying is a big job for the world of education. Character education through the integration of Pancasila student profiles with the Merdeka Curriculum is expected to be able to overcome various juvenile delinquencies that occur. The problem-solving method is implementing a Pancasila student project that is in accordance with the dimensions and elements contained in the Pancasila student project. PKM activities in Pangandaran Regency can help teachers in Pangandaran Regency to carry out Pancasila student projects well, so that students in Pangandaran Regency can be smart and have Pancasila character. During the PKM implementation, the teachers were very enthusiastic and took part in all the training sessions well. There are still many schools that have not implemented the Independent Curriculum and the Pancasila student project through this PKM activity which can be a good first step for teachers in Pangandaran Regency when the time comes to implement the Independent Curriculum and the Pancasila student project. Based on previous studies where there were still some problems in the implementation of the Independent Curriculum and the Pancasila student project, the PKM activities and this research re-emphasized how ideal integration is according to the Ministry of Education and Culture's directions so that the expected goals can be achieved. Keywords: character building; Pancasila student projects; kurikulum merdeka